2019
DOI: 10.1111/1758-2229.12774
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions and neutral processes shape the skin microbiome of European catfish (Silurus glanis) populations of Southwestern France

Abstract: Summary Teleost fishes interact with diverse microbial communities, playing crucial functions for host fitness. While gut microbiome has been extensively studied, skin microbiome has been overlooked. Specifically, there is no assessment of the relative impact of host and environmental factors on microbiome variability as well as neutral processes shaping fish skin microbiome. Here, we assessed the skin microbiome of a Siluriforme, the European catfish (Silurus glanis) sampled in four sites located in Southwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…Amazon River fish were also found to have high Alphaproteobacteria under certain physicochemical conditions [31]. In stark contrast, Gammaproteobacteria dominated the skin microbiome in wild S. salar fry [24], and also that of Silurus glanis, catfish caught in the wild [16]. Of the five instances, the catfish is the only strictly-freshwater inhabitant, but it lacks scales.…”
Section: Freshwater Fish-skin Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…Amazon River fish were also found to have high Alphaproteobacteria under certain physicochemical conditions [31]. In stark contrast, Gammaproteobacteria dominated the skin microbiome in wild S. salar fry [24], and also that of Silurus glanis, catfish caught in the wild [16]. Of the five instances, the catfish is the only strictly-freshwater inhabitant, but it lacks scales.…”
Section: Freshwater Fish-skin Microbiomementioning
confidence: 99%
“…While most of the current research is targeted at fish species with commercial relevance [2,[26][27][28][29] or food safety [30], a few studies have dissected wild fish communities or populations, utilizing deep-sequencing culture-independent methods [15,16,31] and leaving the vast majority of wild habitats unexamined [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the stingrays were collected in the San Diego region, as were the leopard sharks; however, the stingray microbiomes were more similar to the whale shark microbiomes, which were collected in La Paz, Mexico (Supplemental table 1). Similar, environment has been shown to be linked with the skin microbiomes of teleost fishes [49,50] elasmobranchs [33], but these studies have focused on populations of a single species or biogeography, thus limiting insight into possible phylogenetic structure. Our study has leveraged several species, which exhibit varying geography, environment, and trophic positioning.…”
Section: Discussionmentioning
confidence: 99%
“…The water microbiome of shponds were signi cantly distinct and more diverse than the skin and gill microbiomes of both sh, regardless of their age. It is known that free-living microbial communities retain higher richness than host-associated communities [31], with many studies showing a higher bacterial diversity in water relative to sh skin [28,30,36,[58][59][60], gills [14,36], gut [7,15,18,21,61], stomach [36], hindgut [36] and whole larvae [22]. Although some studies in sh have shown that the microbial communities found in the water tend to be recovered in the larval gut microbiome [17,21], others have also shown that water microbiomes do not in uence directly the microbiomes of sh mucosa [7, 8, 13-15, 18, 19, 22, 28, 30, 34, 36, 58-60, 62, 63].…”
Section: Fish and Water Microbiome Comparisonsmentioning
confidence: 99%